Sustainable Business Transformation: Impact of ESG, Green Innovation, and Internal Factors on Corporate Financial Performance - Dahlia Amelia; Majidah Majidah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The company's goal as a business entity is to generate optimal profits in order to provide value to its stakeholders. Achieving this goal reflects the company's performance. The purpose of this study is to determine the effect of environmental, social, and governance (ESG) disclosure, company size, leverage, green innovation, and human resource slack on the company's financial performance in the energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. With purposive sampling, a sample of 42 companies or 210 observational data was obtained. The research data were analyzed using panel data regression through Eviews 13. The results showed that environmental, social, and governance (ESG) disclosure had a positive effect on the company's financial performance. The results of this study are also findings for the energy sector on the IDX and the novelty of this study is in measuring financial performance using the burn rate. These results can be considered by investors in making investment decisions in this sector.